SPE 128544 Hydrate Formation and its Influence on Natural Gas Pipeline Internal Corrosion Rate - Obanijesu, Emmanuel; Pareek, Vishnu; Tade, Moses (Society of Petroleum Engineers, 2010)
Hydrate formation along the natural gas pipeline has been identified as a serious threat to the survival of oil and gas industry. The formation if not quickly removed may plug the flowline to collapse the system. This problem costs the industry billions of dollars in revenue loss annually. While all the available literatures on hydrate formation process have focused on its ability to plug the flow line, there has been little or no recognition of its ability to initiate internal corrosion of the pipeline which is a bigger problem to the industry, hence, the importance of this study. This work focuses on this new area for research interest aimed at revolutionalizing the field of corrosion science and technology.In this study, the composition of the lattice which includes methane (CH4), carbondioxide (CO2) or hydrogen sulphide (H2S) and water molecules (H2O) amongst others is considered. These gases have the ability to easily undergo chemical and/or electrochemical reactions with the pipeline’s internal surface while the lattice is in place. The reaction(s) will easily initiating corrosion of the pipe. The study further identifies the fact that even after the successful removal of the hydrate, the initiated corrosion process may continue with the continuous flow of the fluid within the pipeline thereby leading to gradual degradation of the material and deterioration of the pipe’s integrity. Over time, the pipeline will begin to leak and/or may undergo full bore rupture (FBR). This, apart from the economic consequences will also generate environmental and political consequences and may lead to complete replacement of the pipe-length.Various management schemes including the necessity for the industry to heavily invest in research and development are recommended.